Maqashid Sharia in Islamic Economics and Finance Research - Solihah (SMART Insight, 2021)
Islam has governed all aspects of human life in various fields. be it the social, political, legal, cultural, health and so on. During the development, the bad guys also increased. This is because many business ethics violations do not realize the five basic principles of life; religion, soul, ancestry, logic, and wealth (maqashid Sharia). The purpose of this study is to determine the application of Maqoshid Sharia in the economic or financial aspects of Islamic institutions. This research uses a qualitative approach. To study the content, the authors analyze the information collected through several journals registered in Scopus. The conclusion of this research is that the application of maqoshid sharia has been done well as implemented by Rasulullah SAW, as in maqoshid sharia with four protection systems that have been applied to protect the rights of human rights. but still need a lot of ideas for development. The recommendation of this research is that all aspects of life must be entered into Islamic values that are in accordance with the Sharia to meet the principles of sharia.